Benzothiazole (BTH) Induced Resistance of Navel Orange Fruit and Maintained Fruit Quality during Storage - Huaying Du; Ying Sun; Rui Yang; Wei Zhang; Chunpeng Wan; Jinyin Chen; İbrahim Kahramanoğlu; Liqin Zhu (Journal of Food Quality)
Current research aimed at studying the effect of benzothiazole (BTH) on the fruit quality and resistance against Penicillium italicum (P. italicum). Recently, a synthetically prepared novel BTH was introduced that elicits the induction of resistance against various diseases of fruits. However, little was reported on the effect of BTH on the disease resistance and fruit quality of postharvest navel orange fruit. In this study, 50 mg·L−1 BTH significantly reduced the decay rate of fruits during 36 days of storage at 20 ± 0.5°C (P<0.05). BTH markedly inhibited the weight loss rate in fruits (P<0.05) and effectively maintained higher soluble solid content (SSC), titratable acid (TA), and vitamin C (VC) content compared with control navel orange fruits. Further, BTH significantly suppressed the increase of disease incidence and lesion area of orange fruits challenged with P. italicum (P<0.05). BTH treatment significantly enhanced antioxidant capacity (DPPH, ABTS radical scavenging activity, and reducing power), and superoxide dismutase (SOD) and peroxidase (POD) activities were significantly increased, while the activity of catalase (CAT) was opposite to the former (P<0.05). The activities of β-1,3-glucanase (GLU), phenylalanine ammonia-lyase (PAL), and chalcone isomerase (CHT) were significantly higher in BTH-treated navel orange fruits (P<0.05). Our results suggested that BTH treatment may be a promising treatment for maintaining the quality and inhibiting blue mold of postharvest navel orange in the future.